2009
DOI: 10.1111/j.1365-2036.2009.04089.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of non‐fistulizing (ulcers, stricture) perianal Crohn’s disease in patients treated with infliximab

Abstract: SUMMARY BackgroundIn Crohn's disease, anal ulcers and stricture can be disabling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 31 publications
1
43
0
Order By: Relevance
“…In particular, neither baseline or cavitating ulcers. 25 In both, combination therapy with IFX and an immunomodulator for patients na€ ıve to immunomodulators appeared as an independent predictive factor of response. Although our rate of combination therapy was similar to theirs (75% and 83% respectively), the majority of our patients had been previously treated by immunomodulators: 77% compared to 33% in their study.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, neither baseline or cavitating ulcers. 25 In both, combination therapy with IFX and an immunomodulator for patients na€ ıve to immunomodulators appeared as an independent predictive factor of response. Although our rate of combination therapy was similar to theirs (75% and 83% respectively), the majority of our patients had been previously treated by immunomodulators: 77% compared to 33% in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies, which investigated the results of combined seton and anti-TNF treatment for PFCD, reported a great range of complete response rate between 18-75% (Table IV) [11,12,[15][16][17][18][19][20][21][22][23][24]. Table IV was meticulously prepared only for PFCD.…”
Section: Discussionmentioning
confidence: 99%
“…9 It has been recently shown that patients suffering from nonfistulizing perianal CD may develop anal abscesses under treatment with infliximab. 8,10 But our patient did not suffer from perianal disease in the first appearance of the disease, and perianal disease appeared when she was under treatment with infliximab (and under sustained remission). This type of complication is quite surprising.…”
mentioning
confidence: 89%